Caffeic acid treatment promotes the accumulation of flavonoids in fresh‐cut pineapple by histone lysine methylation regulation - Jing Zeng; Ting Li; Mengting Liu; Jiechun Peng; Hanzhi Liang; Ruiming Zhong; Yao Peng; Mengyao Wu; Jiangtao Zhang; Xuewu Duan; Xinquan Yang (Food Frontiers)
Abstract Fresh‐cut pineapple is highly popular with consumers, but it is also susceptible to quality deterioration during storage or shelf life. This study aimed to explore the effects of caffeic acid on the quality of fresh‐cut pineapple, specifically in relation to epigenetic regulation. The application of caffeic acid efficiently maintained fruit quality of pineapple slices stored at 4°C. Interestingly, caffeic acid treatment resulted in the increased accumulation of flavonoids in fresh‐cut pineapple. Moreover, the expression of several flavonoids biosynthesis‐related genes (AcPAL, AcF3’H, AcCHI, AcCHS2, Ac4CL, and AcFLS) was upregulated by caffeic acid. Furthermore, caffeic acid increased the methylation levels of H3K4me3, a gene‐activated epigenetic marker, at the loci of AcF3’H, AcCHI, AcCHS2, Ac4CL, and AcFLS. Overall, these findings suggest that the treatment with caffeic acid leads to increased levels of H3K4me3 and activates the expression of flavonoids biosynthesis‐related genes, thereby promoting the accumulation of flavonoids and maintaining the quality of pineapple slices.